Sugar Metabolism of Scardovia wiggsiae, a Novel Caries-Associated Bacterium - Kameda, Mai; Abiko, Yuki; Washio, Jumpei; Tanner, Anne C. R.; Kressirer, Christine A.; Mizoguchi, Itaru; Takahashi, Nobuhiro (Frontiers in Microbiology, 2020)
Scardovia wiggsiae has been detected from caries in children and adolescents and has been suggested to be a caries-associated microorganism. To investigate the cariogenic potential of S. wiggsiae, we examined carbohydrate metabolism and acid productivity, the fluoride sensitivity of carbohydrate metabolism and the mechanism by which fluoride inhibits carbohydrate metabolism, and the acid sensitivity of carbohydrate metabolism in this bacterium. S. wiggsiae metabolized glucose and reduced the environmental pH to 3.5. It mainly produced acetic acid from glucose, together with small amounts of lactic and formic acid. The 50% inhibitory concentration of fluoride for acid production was 8.0 mM at pH 7.0 and 1.5 mM at pH 5.5, which were much higher than those of representative caries-associated bacteria, such as Streptococcus mutans. Metabolomic profiles showed the accumulation of 3-phosphoglycerate and a marked reduction in the pyruvate concentration in the presence of fluoride, suggesting that fluoride inhibits the latter half of glycolysis, including enolase activity. Enolase activity was inhibited by fluoride in S. wiggsiae, but it was more fluoride-tolerant than the enolase activity of S. mutans. Unlike in S. mutans, lactic acid did not inhibit acid production by S. wiggsiae at acidic pH. These results indicate that S. wiggsiae exhibits high acid production and tolerance to fluoride and lactic acid. S. wiggsiae possesses a unique metabolic pathway, the F6PPK shunt, which might allow it to avoid the lactate-formate pathway, including fluoride-sensitive enolase activity, and enable metabolic flow to the fluoride-tolerant acetate pathway. The fluoride tolerance of S. wiggsiae’s enolase activity also increases the fluoride tolerance of its carbohydrate metabolism. The lactic acid tolerance of S. wiggsiae’s acid production might result in S. wiggsiae having high acidogenic and aciduric potential and make it ecologically competitive in acidic environments, such as caries lesions, where lactic acid predominates.